« Il futuro ha un cuore antico » : parcours historique des discours sur l’intercompréhension entre langues romanes - Francisco Javier Calvo Del Olmo (Revue des Langues Romanes)
The perception of distance and proximity between Romance languages has been constant since the Middle Ages (Wright, 1989). Thus, Romance linguistics, as a modern science, are based on the application of the historical-comparative method (Posner, 1998). Based on these observations, we present the epilinguistic speech of several intellectuals (such as Raynouard, Mistral, Bréal, Gaston Paris, Ronjat, Jaurès, Saussure and Eco) which preceded the development of intercomprehension at the end of the 1990s. , as a strictly educational approach (Candelier, 2009). Ultimately, we hope that our study will help building a space for mutual understanding.